Influence of cobalt chromium alloy surface modification on the roughness and wettability behavior of pine oil/hydroxyapatite as coating. (7th November 2018) - Vechietti, F A; Muniz, N O; Rezwan, K; Schumacher, M; Gelinsky, M; dos Santos, L A Loureiro
Abstract: In this study, hydroxyapatite (HAp) was mixed with pine oil (PO) to coat Co–15Cr–15W–10Ni alloy via brushing method and subsequent heat treatment. Four different surfaces were coated to assess the influence of the roughness on wettability properties and interaction between substrate and coating. The coated substrates were characterized by using x-ray diffraction (XRD), scanning electron microscopy (SEM), profilometer analysis, wettability and scratch resistance. The contact angle of water on the metal implant surfaces was much higher (68 °C) than that of PO (23°), allowing a more homogeneous coating process when PO was used for HAp suspension. The effect of heat treatment on the metal-coating bonding strength also was evaluated. Thermal and chemical analyzes corroborated that after heat treatment there was no evidence of PO and only phases related to pure hydroxyapatite were detected. An interaction between substrate and coating was obtained for all surface morphologies, however, the smoother surfaces showed better adhesiveness than the rougher ones. This novel HAp coating method is expected to be suitable for medical applications due to its high potential as alternative to complex and expensive conventional coating methods.